Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1981
DOI: 10.1111/j.1095-8649.1981.tb03753.x
|View full text |Cite
|
Sign up to set email alerts
|

Peculiarities of sperm production by anadromous and parr Atlantic salmon (Salmo salar L.) and fish cultural characteristics of such sperm

Abstract: This study describes peculiarities of sperm production by anadromous and precocious parr Atlantic salmon. It was possible to obtain 15 sperm samples with total volume of 130 cm3 from anadromous males at the peak of the spawning run. Changes in the sperm characteristics with the increase of the sea-life age and weight of anadromous males are shown. Such changes are also shown throughout the spawning period. The properties of parr spermatazoa were investigated and it is suggested that these spermatozoa are suita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 3 publications
3
26
0
Order By: Relevance
“…Mechanisms for competition range from multiple copulation to larger ejaculates, depending on the capacity to store sperm, but in species with external fertilization sperm placement can also be optimized, and this is probably the main challenge to mature parr. Studies on the characteristics of ejaculates from parr and migrant males (Kazacov 1981) found that sperm concentration and activity did not differ between these male types and that the average ejaculate size of migrant males is 20-30 times as large as the ejaculate volume of parr, larger than the parr's total gonad weight. Furthermore, parr allocate a larger fraction of their energies to reproduction (Gage et al 1995), having gonadosomatic indexes (gonad weight\total body weight) of around 4.65 % compared with only 2.33 % in migrant males.…”
Section: Discussion and Conclusion (A) Parr Body Size And Reproductimentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanisms for competition range from multiple copulation to larger ejaculates, depending on the capacity to store sperm, but in species with external fertilization sperm placement can also be optimized, and this is probably the main challenge to mature parr. Studies on the characteristics of ejaculates from parr and migrant males (Kazacov 1981) found that sperm concentration and activity did not differ between these male types and that the average ejaculate size of migrant males is 20-30 times as large as the ejaculate volume of parr, larger than the parr's total gonad weight. Furthermore, parr allocate a larger fraction of their energies to reproduction (Gage et al 1995), having gonadosomatic indexes (gonad weight\total body weight) of around 4.65 % compared with only 2.33 % in migrant males.…”
Section: Discussion and Conclusion (A) Parr Body Size And Reproductimentioning
confidence: 99%
“…The fact that, in section 8, where two sets of six parr were allowed to spawn consecutively with the anadromous pair, parr success increased when new parr were added, can be taken as evidence that the decrease in success in the second egg pocket was not due to an increase in the aggressiveness of the anadromous male or female, as the same migrant pair experienced an increase in parr success when new parr replaced the old. Unfortunately, there is a scarcity of data on spermatogenesis in mature male parr, although there is some evidence that sperm production is enhanced during the spawning period (Kazacov 1981).…”
Section: Discussion and Conclusion (A) Parr Body Size And Reproductimentioning
confidence: 99%
“…We found no effect of male size on fertilization success where behavioral competition, sperm competition and spawning history were eliminated as contributing factors. Larger males may have had greater ejaculate volumes (Kazakov 1981, Gjerde 1984; however, this apparently did not benefit larger males in our study, probably because ejaculate volumes of small males were more than adequate for maximum fertilization (Hoysak & Liley 2001).…”
Section: Discussionmentioning
confidence: 51%
“…In nematodes and teleosts, males therefore appear to be penalized less by small size (Charnov & Bull 1977, Conover 1984. For example, whereas gamete production in teleosts may be relatively unconstrained by male body size (Kazamov 1981), fecundity is known to increase with maternal size (e.g., Bagenal1966, Docker et al 1986, Hay & Brett 1988. Egg number and female length are likewise correlated in lampreys (Hardisty 1964, Kott 1971, Beamish & Thomas 1983, Docker & Beamish 1991).…”
Section: Streammentioning
confidence: 99%